Immunogenicity and safety of the fourth dose of quadrivalent human papillomavirus (HPV) vaccine in immunosuppressed women who did not seroconvert after three doses - Moreira dos Santos, Lívia Zignago; Rodrigues, Camila Cristina Martini; Miyaji, Karina Takesaki; Infante, Vanessa; Picone, Camila de Melo; Lara, Amanda Nazareth; Eklund, Carina; Kann, Hanna; Dillner, Joakim; Mayaud, Philippe; Sartori, Ana Marli Christovam (Frontiers in Cellular and Infection Microbiology, 2024)
IntroductionImmunocompromised persons have high risk of persistent human papillomavirus (HPV) infection and HPV-related diseases, and lower immune response to vaccines. This study evaluated the immunogenicity and safety of administering a fourth dose of quadrivalent (4v)HPV vaccine in immunosuppressed women who did not seroconvert after three doses.MethodsAn open-label, not-controlled trial included immunosuppressed women (solid organ transplant patients and women receiving treatment for SLE) who did not seroconvert to at least one of the four HPV vaccine types after three 4vHPV vaccine doses. All participants received a fourth 4vHPV vaccine dose (median 27 months after third dose). Immunogenicity was evaluated a month after the fourth dose, by measuring seroconversion rates and antibody geometric mean concentration (GMC).ResultsTwenty-three women were included. Among women who did not seroconvert for each vaccine type after three doses, 2/10 seroconverted to HPV6, 3/10 to HPV11, 3/10 to HPV16 and 6/18 to HPV18, after the fourth 4vHPV dose. There was an increase in antibody GMC for HPV 6, 16, 18, with highest increase for HPV16 (from 6.02 to 44.63 International Units). There was no increase of anti-HPV-11. Within seven days after vaccination, only three of the 23 vaccinees reported any adverse event, none of which were classified as serious.ConclusionsAlthough safe, the fourth 4vHPV vaccine dose led to seroconversion in only few immunosuppressed women who had not seroconverted after three doses.